Investigation of student experiences with ChatGPT-supported online learning applications in higher education - Kayalı, Bünyami; Yavuz, Mehmet; Balat, Şener; Çalışan, Mücahit (Australasian Journal of Educational Technology, 2023)
The purpose of this study was to determine university students' experiences with the use of ChatGPT in online courses. The sample consisted of 84 associate degree students from a state university in Turkey. A multi-method approach was used in the study. Although quantitative data were collected using the Chatbot Usability Scale, qualitative data were collected using a semi-structured interview form that we developed. The data were analysed using descriptive and content analysis methods. According to the findings, ChatGPT exhibits advantages such as a user-friendly interface and fast, concise, relevant responses. Moreover, emphasizing its contribution to the learning process, the information provided was sufficient and topic-oriented. The understandability of the chatbot’s functions and the clarity of their communication were emphasized. However, there are disadvantages such as performance issues, frequency of errors and the risk of providing misleading information. Concerns have also been raised about the potential difficulties chatbots may face in ambiguous conversations and providing insufficient information on privacy issues. In conclusion, ChatGPT is recognised as a potentially valuable tool in education based on positive usability impressions; however, more research is needed for its safe use. Implications for practice or policy Based on positive usability impressions, students and instructors can use ChatGPT to support educational activities. ChatGPT can promote and enhance students' personalised learning experiences. ChatGPT can be used in all higher education courses. Users should be cautious about the accuracy and reliability of the answers provided by ChatGPT. Decision-makers should take precautions against risks such as privacy, ethics, confidentiality and security that may arise from using artificial intelligence in education.